1991
DOI: 10.1002/hep.1840140415
|View full text |Cite
|
Sign up to set email alerts
|

Screening for candidate hepatic growth factors by selective portal infusion after canine Eck’s fistula

Abstract: Completely diverting portacaval shunt (Eck's fistula) in dogs causes hepatocyte atrophy, disruption of hepatocyte organelles, fatty infiltration and low-grade hyperplasia. The effect of hepatic growth regulatory substances on these changes was assessed by constantly infusing test substances for four postoperative days after Eck's fistula into the detached left portal vein above the shunt. The directly infused left lobes were compared histopathologically with the untreated right lobes. In what has been called a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…HSS protects the liver from the hepatic agent CCl 4 and galactosamine against fibrosis (Gao and Zhou, 2005; Li et al, 2011). The liver regeneration enhancer ALR can inhibit liver atrophy induced by Eck’s fistula (portal vein and inferior vena cava anastomosis) (Rosemurgy et al, 2002; Francavilla et al, 2010; Zeng et al, 2010; Xi et al, 2013). The results of the study showed that these factors can effectively protect the liver from further damage in vivo and improve animal survival by promoting hepatocyte DNA synthesis and liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…HSS protects the liver from the hepatic agent CCl 4 and galactosamine against fibrosis (Gao and Zhou, 2005; Li et al, 2011). The liver regeneration enhancer ALR can inhibit liver atrophy induced by Eck’s fistula (portal vein and inferior vena cava anastomosis) (Rosemurgy et al, 2002; Francavilla et al, 2010; Zeng et al, 2010; Xi et al, 2013). The results of the study showed that these factors can effectively protect the liver from further damage in vivo and improve animal survival by promoting hepatocyte DNA synthesis and liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Francavilla et al [35] utilized a canine Eck fistula model in 1991, infusing T 3 , glucagon, prolactin, angiotensin II, vasopressin, norepinephrine, estradiol, IGF-II, HSS, TGF-α, HGF (also termed hepatopoietin-A), EGF, TGF-β, tamoxifen, IL-1, IL-2 and insulin into one of the detached portal vein branches above the shunt [35]. Insulin and partly T 3 , IGF-II, HSS, TGF-α and HGF inhibited liver atrophy.…”
Section: The Evolution Of the ‘Humoral Theory’mentioning
confidence: 99%